2012
DOI: 10.1111/1756-185x.12016
|View full text |Cite
|
Sign up to set email alerts
|

Disease patterns of rheumatology outpatients seen in a tertiary hospital serving a multi‐ethnic, urban Asian population in Singapore

Abstract: Rheumatoid arthritis, osteoarthritis and crystal arthritis were the three most common rheumatological diseases seen in a tertiary referral centre serving a multi-ethnic urban Asian population in Singapore.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 17 publications
4
12
2
Order By: Relevance
“…In the present study the most common rheumatic disease was rheumatoid arthritis 60.5%, followed by systemic lupus erythematosus 12.5%, gouty arthritis 8.9% and osteoarthritis 3.3% of patients, similarly Ng et al [7] showed a higher prevalence of rheumatoid arthritis and SLE in a study conducted in Singapore. In contrast to the current study, community-based studies [8] revealed that the osteoarthritis is the most common rheumatic disorder, this can be explained by the relatively young age group in the current study as well as the fact that most cases of osteoarthritis are treated by orthopedic surgeons or general physicians and not usually referred to rheumatic clinics.…”
Section: Discussionsupporting
confidence: 79%
“…In the present study the most common rheumatic disease was rheumatoid arthritis 60.5%, followed by systemic lupus erythematosus 12.5%, gouty arthritis 8.9% and osteoarthritis 3.3% of patients, similarly Ng et al [7] showed a higher prevalence of rheumatoid arthritis and SLE in a study conducted in Singapore. In contrast to the current study, community-based studies [8] revealed that the osteoarthritis is the most common rheumatic disorder, this can be explained by the relatively young age group in the current study as well as the fact that most cases of osteoarthritis are treated by orthopedic surgeons or general physicians and not usually referred to rheumatic clinics.…”
Section: Discussionsupporting
confidence: 79%
“…Although only limited epidemiological data are available from Asia, prevalence rates are believed to be low (0.02% in China) . In Singapore, PsA patients constituted 4% of outpatients with rheumatologic conditions at a tertiary hospital …”
Section: Introductionmentioning
confidence: 99%
“…1 In Singapore, PsA patients constituted 4% of outpatients with rheumatologic conditions at a tertiary hospital. 2 Disease severity may range from mild to severe and erosive, deforming arthritis. PsA is also associated with metabolic syndrome and a higher risk of cardiovascular death.…”
Section: Introductionmentioning
confidence: 99%
“…Data from Asia are limited but appear to be similar . Patients with PsA constituted approximately 4% of outpatients with rheumatologic diseases in a cross‐sectional study at a tertiary hospital in Singapore …”
Section: Introductionmentioning
confidence: 99%
“…1 Patients with PsA constituted approximately 4% of outpatients with rheumatologic diseases in a cross-sectional study at a tertiary hospital in Singapore. 2 PsA is heterogeneous, ranging from mild disease to erosive and deforming arthritis, and affects about 30% of individuals with psoriasis. 3 Untreated disease results in progressive joint damage, disability, decreased health-related quality of life (HRQoL) and increased mortality 4 comparable to rheumatoid arthritis (RA).…”
Section: Introductionmentioning
confidence: 99%